Intraneural ganglion cyst of the peroneal nerve occurring after coronavirus disease-19 vaccination: A case report - Nackhwan Kim (Taylor & Francis Group, 2023)
Ganglion cysts are relatively common, but intraneural ganglion cysts (INGCs) within peripheral nerves are rare and poorly understood. We present the case of a 58-year-old woman who presented with acute right-foot drop. She experienced acute knee pain radiating from the lateral leg to the dorsal foot two days after the first coronavirus disease-19 (COVID-19) vaccination (BNT162b2, Pfizer-BioNTech). She had no history of trauma or medication use. Two weeks after the onset of symptoms, she developed a dorsiflexor weakness of the right foot (Medical Research Council grade, poor). The weakness worsened to a "trace" grade despite providing conservative management for one month. Ultrasonography revealed a fusiform echolucent structure within the course of the right common peroneal nerve around the fibular head. Magnetic resonance imaging revealed multiple intraneural cysts within the right common peroneal nerve. Nerve conduction and electromyographic studies revealed multiphasic motor unit action potentials accompanied by abnormal spontaneous activities in the innervated muscles, along with axonal degeneration of the deep peroneal nerves. Surgical removal of the cyst was performed, and the patient's symptoms gradually improved. Pathological examination revealed a cystic structure containing mucinous or gelatinous fluid and lined with flattened or cuboidal cells. The clinical course and sequential electromyographic findings relevant to this symptomatic cyst were temporally related to the vaccination date. The present case suggests that INGC-induced peroneal palsy is a possible complication after COVID-19 vaccination.